Accuracy of magnetic resonance enterography in the preoperative assessment of patients with Crohn's disease of the small bowel. (May 2017) - Pous‐Serrano, S.; Frasson, M.; Palasí Giménez, R.; Sanchez‐Jordá, G.; Pamies‐Guilabert, J.; Llavador Ros, M.; Nos Mateu, P.; Garcia‐Granero, E.
Abstract: Aim: To assess the accuracy of magnetic resonance enterography in predicting the extension, location and characteristics of the small bowel segments affected by Crohn's disease. Method: This is a prospective study including a consecutive series of 38 patients with Crohn's disease of the small bowel who underwent surgery at a specialized colorectal unit of a tertiary hospital. Preoperative magnetic resonance enterography was performed in all patients, following a homogeneous protocol, within the 3 months prior to surgery. A thorough exploration of the small bowel was performed during the surgical procedure; calibration spheres were used according to the discretion of the surgeon. The accuracy of magnetic resonance enterography in detecting areas affected by Crohn's disease in the small bowel was assessed. The findings of magnetic resonance enterography were compared with surgical and pathological findings. Results: Thirty‐eight patients with 81 lesions were included in the study. During surgery, 12 lesions (14.8%) that were not described on magnetic resonance enterography were found. Seven of these were detected exclusively by the use of calibration spheres, passing unnoticed at surgical exploration. Magnetic resonance enterography had 90% accuracy in detecting the location of the stenosis (75.0% sensitivity, 95.7% specificity). Magnetic resonance enterography did not precisely diagnose the presence of an inflammatory phlegmon (accuracy 46.2%), but it was more accurate in detecting abscesses or fistulas (accuracy 89.9% and 98.6%, respectively). Conclusion: Magnetic resonance enterography is a useful tool in the preoperative assessment of patients with Crohn's disease. However, a thorough intra‐operative exploration of the entire small bowel is still necessary.